Performance Analysis of Hybrid Push/Pull Production Systems - Khokhajaikiat, Dr.Porntep (Engineering and Applied Science Research, 2013)
In this paper, simulation modeling was employed to carry out the best operating control policy for the multistage series/parallel production system of hair dryer. The effects of different control policies representing push, pull, and hybrid push/pull policies on the system performances e.g. throughput rate, raw material and work-in-process (WIP) inventory, and lost sale of the production system are considered. The results indicate that the hybrid policy of push strategy at the upstream stages and pull strategy at the downstream stage has yielded the best performances. The batch size has significantly affected on the lost sale of production system. Moreover, the number of Kanbans for stages controlled by pull strategy is determined in the study.